A social semiotic approach to identifying critical aspects. Issue 3 (13th July 2015) - Fredlund, Tobias; Linder, Cedric; Airey, John
Abstract : Purpose: – The purpose of this paper is to propose a social semiotic approach to analysing objects of learning in terms of their critical aspects. Design/methodology/approach: – The design for this paper focuses on how the semiotic resources – including language, equations, and diagrams – that are commonly used in physics teaching realise the critical aspects of a common physics object of learning. A social semiotic approach to the analysis of a canonical text extract from optics is presented to illustrate how critical aspects can be identified. Findings: – Implications for university teaching and learning of physics stemming from this social semiotic approach are suggested. Originality/value: – Hitherto under-explored similarities between the Variation Theory of Learning, which underpins learning studies, and a social semiotic approach to meaning-making are identified. These similarities are used to propose a new, potentially very powerful approach to identifying critical aspects of objects of learning.